Gingivectomy and gingivoplasty surgery in cases of inflammatory gingival enlargement: Bedah gingivektomi dan gingivoplasti pada kasus inflammatory gingival enlargement - Arnov, Steffi Triany; Nabila, Farah Kanza; Fauziah, Mutia Nurul; Pratama, Julian (Makassar Dental Journal, 2025)
Gingival enlargement can be caused by plaque accumulation, triggering inflammation of the gingiva that affects aesthetics and makes cleaning difficult. This condition needs to be treated as early as possible with gingivectomy and gingivoplasty. This article describes the procedures of gingivectomy and gingivoplasty in patients with gingival enlargement accompanied by poor oral hy-giene. A 19-year-old woman came to Unimus Dental Hospital complaining of enlarged anterior gums that bled when brushing her teeth. Clinical examination revealed rounded, reddened gums with an unstippled texture and soft consistency, no recession, BOP (+) on certain teeth, and grade 0 mobility. Panoramic radiography showed no bone resorption. Conventional gingivectomy and gingivoplasty were performed on teeth 12, 11, 21, 22, and 42. At the 2-week postoperative check-up, the gums were no longer inflamed, with the gingival margin following the contour of the teeth, and there was a noticeable difference before and after gi-ngivectomy. The patient had no complaints or pain. It was concluded that the gingivectomy procedure provided satisfactory re-sults for the patient both aesthetically and medically.